Linear State-Feedback Primary Control for Enhanced Dynamic Response of AC Microgrids - Perez-Ibacache, Ricardo; Silva, Cesar A.; Yazdani, Amirnaser (IEEE transactions on smart grid, 2019)
This paper proposes a state feedback primary control strategy for microgrids with multiple distributed energy resource units, improving their transient behavior in both islanded and grid-connected modes of operation. To that end, the interaction of each distributed energy resource unit within the microgrid is modeled as a lumped dynamic system, which results to be nonlinear and multivariable. For the closed-loop control of such multivariable systems, the full state feedback formulation is preferred which requires a suitable state observer. For the design of the observer and feedback gains, the solution of the linear-quadratic estimation and regulation problems is considered. For simplicity, an approximate linear model at a representative operating point is derived. The linear quadratic Gaussian/loop-transfer recovery is adopted as the design procedure to optimize the trajectory of the state variables subject to a desirable actuation effort, in this case of the voltage amplitude and frequency, yielding a solution that is robust to model uncertainties. The effectiveness of the strategy is assessed through time-domain simulation on the CIGRE benchmark medium-voltage distribution network with three distributed energy resource units. These results are compared to those obtained with conventional static droop gains and with a state-of-the-art technique from the literature.